2005
DOI: 10.1007/s10620-005-3050-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adenosine Deaminase, Superoxide Dismutase, and Catalase Activities with Helicobacter pylori

Abstract: Our purpose was to investigate associations between adenosine deaminase (ADA), superoxide dismutase (SOD), and catalase (CAT) activities and H. pylori.Ninety-nine patients were studied. Eight antral mucosal biopsies were taken for biochemical assessment of ADA, CAT, AND SOD activity and histological assessment. H. pylori density wAS evaluated according to the updated Sydney system. Patients were divided into three groups according to Sydney classification. ADA activity was found to be higher in patients having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…In concordance with the present results, Götz et al (41) reported an increase in MnSOD activity and a slight decrease in Cu/ZnSOD in the inflamed gastric mucosa in HP-infected gastric patients, while Bulbuloglu et al (42) highlighted an increase in total SOD activity in patients with different states of HP infection, as confirmed by the absence of changes recorded in our HP-negative CG samples.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In concordance with the present results, Götz et al (41) reported an increase in MnSOD activity and a slight decrease in Cu/ZnSOD in the inflamed gastric mucosa in HP-infected gastric patients, while Bulbuloglu et al (42) highlighted an increase in total SOD activity in patients with different states of HP infection, as confirmed by the absence of changes recorded in our HP-negative CG samples.…”
Section: Discussionsupporting
confidence: 93%
“…Tissue damage results from the cytotoxic effects of ammonia or the indirect effect of urease-induced stimulation of the inflammatory response, including recruitment of leukocytes, induction of proinflammatory cytokines, and triggering of an oxidative burst of neutrophils (42).…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have reported that no CAT activity was found in most gastric juices, probably because of their low pH levels, and in some antral tissue specimens 41,42. Akcan, et al2 reported no unchanged of MPO and SOD activity in gastric mucosa of childhood period with HP (+) and (-) subjects, and Bulbuloglu, et al42 also reported no unchanged of CAT activity in antral mucosal between HP (+) and (-) subjects. In the present study, MPO and CAT activities were similar between the subjects included in the study.…”
Section: Discussionmentioning
confidence: 95%
“…Almost all the previous studies on the association of with HP in adult population were performed in gastric mucosa 12,21,23. Some previous studies have reported that no CAT activity was found in most gastric juices, probably because of their low pH levels, and in some antral tissue specimens 41,42. Akcan, et al2 reported no unchanged of MPO and SOD activity in gastric mucosa of childhood period with HP (+) and (-) subjects, and Bulbuloglu, et al42 also reported no unchanged of CAT activity in antral mucosal between HP (+) and (-) subjects.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of serum ADA have been reported in infectious diseases such as viral and bacterial pneumonia, HIV infection, extra-pulmonary and pulmonary tuberculosis, H. pylori , acute appendicitis, visceral leishmaniasis, and mononucleosis [11,12,22,23] and might have diagnostic value. Moreover, circulating levels of ADA have been shown to increase in several inflammatory conditions, including Behçet’s disease, systemic lupus erythematosus, rheumatoid arthritis, and certain malignancies, especially those of hematopoietic origin [2434].…”
Section: Discussionmentioning
confidence: 99%